The Effect of Financial Performance on Capital Structure : Study of Pecking Order Theory - Eni Puji Estuti; Irene Rini Demi Pangestuti (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Capital structure is an interesting variable to discuss because it is related to company management decisions. This funding decision will have an impact on good or bad financial condition of a company. The impact, among other things, when a company uses debt that is inflated, can result in the company bearing a large burden, meaning that the company's financial risk will increase. This study aims to analyze the effect of asset structure, profitability, company size, liquidity and sales growth on the capital structure of household goods and cosmetic companies listed on the Indonesia Stock Exchange (IDX). This research wants to see the existence of companies that produce basic necessities and are demanded by consumers even when the economy is not good. The results of this study indicate that asset structure, liquidity and sales growth have no effect on capital structure. Profitability, company size has a positive and significant influence on capital structure. These results prove that the pecking order theory is still the company's choice in determining the capital structure. Keywords : Pecking order theory, capital structure, financial decision